2020
DOI: 10.1017/s0031182020002231
|View full text |Cite
|
Sign up to set email alerts
|

Transmission networks and ectoparasite mite burdens in Oecomys paricola (Rodentia: Cricetidae)

Abstract: The host contact network structure results from the movement and behaviour of hosts (e.g. degree of sociability; vagility and greater or lesser fidelity of shelters), which can generate heterogeneity in the transmission of parasites and influence the parasitic burden of individual hosts. In the current study, we tested the hypothesis that the burdens of Gigantolaelaps oudemansi mites are related to the characteristics of the transmission networks of individuals of Oecomys paricola, a solitary rodent. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A growing number of studies have focused on the phylogeography and population genetic relationships of rodent hosts and their associated ectoparasites showing that factors such as host switching [ 8 10 ], social structure of the hosts [ 11 13 ], and the closeness of the relationship between the host and its parasite (e.g. host specificity, [ 14 – 16 ]) determine the structure of parasitic populations.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have focused on the phylogeography and population genetic relationships of rodent hosts and their associated ectoparasites showing that factors such as host switching [ 8 10 ], social structure of the hosts [ 11 13 ], and the closeness of the relationship between the host and its parasite (e.g. host specificity, [ 14 – 16 ]) determine the structure of parasitic populations.…”
Section: Introductionmentioning
confidence: 99%
“…What could be the mechanism of non-linear changes in flea abundance? An increase in host density leads to increased contact rates among individuals, and higher probability of parasite transmission (Côté & Poulin 1995;Sih et al 2018;Fernandes et al 2021). In our study system, the potential for higher contact rates at high host densities is indicated by increased home range overlap that occurs in yellow-necked mice after mast years (Bogdziewicz et al 2016c).…”
Section: Discussionmentioning
confidence: 77%
“…2018; Fernandes et al. 2021). In our study system, the potential for higher contact rates at high host densities is indicated by increased home range overlap that occurs in yellow‐necked mice after mast years (Bogdziewicz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that the potential transfer of ectoparasites from generalist rodents to humans and domesticated animals is greater than from specialist rodents given their more frequent interactions with human populations (Vargas‐Sandoval et al., 2014), there is a need to increase our understanding of the spatial dynamics of transmission from host to host. Higher densities of rodents mean closer spatial proximity between individuals, which could lead to host‐to‐host ectoparasite transmission (Fernandes et al., 2021; Webber et al., 2015). We propose that this could be tested through the spatial segregation patterns of rodents with and without ectoparasites.…”
Section: Introductionmentioning
confidence: 99%